Improvement of a tissue maceration technique for the determination of placental involvement in schistosomiasis. - Martha Charlotte Holtfreter; Heinrich Neubauer; Tanja Groten; Hosny El-Adawy; Jana Pastuschek; Joachim Richter; Dieter Häussinger; Mathias Wilhelm Pletz; Benjamin Thomas Schleenvoigt (PLoS Neglected Tropical Diseases, 2017)
Schistosomiasis in pregnancy may cause low birth weight, prematurity and stillbirth of the offspring. The placenta of pregnant women might be involved when schistosome ova are trapped in placental tissue. Standard histopathological methods only allow the examination of a limited amount of placental tissue and are therefore not sufficiently sensitive. Thus, placental schistosomiasis remains underdiagnosed and its role in contributing to schistosomiasis-associated pregnancy outcomes remains unclear. Here we investigated an advanced maceration method in order to recover a maximum number of schistosome ova from the placenta. We examined the effect of different potassium hydroxide (KOH) concentrations and different tissue fixatives with respect to maceration success and egg morphology. Placental tissue was kept either in 0.9% saline, 5% formalin or 70% ethanol and was macerated together with Schistosoma mansoni infested mouse livers and KOH 4% or 10%, respectively. We found that placenta maceration using 4% KOH at 37°C for 24 h was the most effective method: placental tissue was completely digested, egg morphology was well preserved and alkaline concentration was the lowest. Ethanol proved to be the best fixative for this method. Here we propose an improved maceration technique in terms of sensitivity, safety and required skills, which may enable its wider use also in endemic areas. This technique may contribute to clarifying the role of placental involvement in pregnant women with schistosomiasis.